Guidelines for chemical reactivity evaluation and application to process design. (Center for Chemical Process Safety of the American Institute of Chemical Engineers, 1995)
Drawn from international sources, this book provides principles and strategies for the evaluation of chemical reactions, and for using this information in process design and management. A useful resource for engineers who design, start-up, operate, and manage chemical and petrochemical plants, the book places special emphasis on the use of state-of-the-art technology in theory, testing methods, and applications in design and operations.
Keywords: Chemical processes.; Reactivity (Chemistry); elektronické knihy; electronic books